2023
DOI: 10.3389/fcomm.2023.1023594
|View full text |Cite
|
Sign up to set email alerts
|

Pains and portends: A collaborative autoethnography of engineering faculty navigating gendered cultures

Abstract: This mediated collaborative autoethnography uses reproduced dialogue, poetic inquiry, and composite, fictionalized narratives to story the gendered experiences of two instructional faculty teaching a coordinated engineering class and working in an undergraduate engineering program at a large public university. The contrasting, gendered narratives of the engineering faculty storied in this paper illuminate several themes: (1) discourses of gendered relational labor (masculinized savior vs. feminized emotional w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Other research has found that minoritized students often find themselves without mentors and are the first in their families to navigate the bureaucracies of colleges and institutions of higher education [Cromley et al, 2016;Whitaker & Montgomery, 2012]. Yet, they also find themselves emerging as role models for others younger than themselves [Miller et al, 2023].…”
Section: Engineering Students Of Color Use the Most Cultural Assetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research has found that minoritized students often find themselves without mentors and are the first in their families to navigate the bureaucracies of colleges and institutions of higher education [Cromley et al, 2016;Whitaker & Montgomery, 2012]. Yet, they also find themselves emerging as role models for others younger than themselves [Miller et al, 2023].…”
Section: Engineering Students Of Color Use the Most Cultural Assetsmentioning
confidence: 99%
“…The cultural foundations which engineering curricula, engineering colleges, and engineering workplaces all share can trace their roots to the early 20th Century. Frehill (2004) conducted archival research and found that engineering was couched as a masculine space to "prove manhood," ultimately creating unwelcoming or hostile environments for People of Color and White women through the present [Miller et al, 2023]. As a long-lasting consequence, typical engineering curricula in the 21st Century are entrenched with hidden elements [Polmear et al, 2019;Villanueva, 2018] that discourage the participation of marginalized people.…”
Section: Introductionmentioning
confidence: 99%